Strength and Deformation Characteristics of Re-Deposited Lahar from Mt. Pinatubo. - Orense, Rolando P.
The 1991 eruption of Mt. Pinatubo caused extensive damage, with subsequent lahar flows covering widespread areas. Rehabilitation and reconstruction activities are currently being undertaken, with new buildings and other civil engineering structures being built over lahar covered areas and roadway/river embankments being constructed using lahar materials. However, there is insufficient knowledge regarding the geotechnical properties of these volcanic deposits, especially their strength and deformation characteristics. To address this issue, an extensive research program was performed in order to investigate the geotechnical characteristics of freshly re-deposited lahar deposits from Mt. Pinatubo and to understand their behavior as materials for geotechnical construction. Freshly re-deposited samples were obtained at two locations : one upstream and another downstream from the volcano. In addition to engineering properties, permeability and compaction characteristics, the strength and deformation behavior in drained condition were investigated uisng the hollow torsional shear apparatus, with emphasis on the effects of relative density and confining pressure on the shear stress and volumetric change behavior. Moreover, the response of Pinatubo lahar during seismic loading was investigated by determining their cyclic deformation properties and liquefaction resistance. The findings obtained in this study can be used to formulate appropriate design methodology on the use of re-deposited lahar as geotechnical materials.